The administrative structure of Silesia as a determinant of legal and constitutional cohesion (12th–15th century) - Pauk, Marcin; Wółkiewicz, Ewa (Publishing House eBooki.com.pl, 2013)
An analysis of crucial legal and systemic issues indicates that the most important aspect in the formation of Silesian regional cohesion was the ‘transformation’ that took place in the 13th century, including the reception of German law and the institution of the self-governing municipality. The main factor determining the functionality of administrative and judicial structures was the proceeding territorial fragmentation. In the 12th century the provincial comites, appointed by the principes, as well as the Bishops of Wrocław, performed the function of intermediaries between Silesia and the rest of the monarchy. After 1163, the Silesian dukes concentrated on the particular needs of their territorial dominions that were taking shape, and were sometimes also used as power bases for carrying out state-wide political concepts. Hence the initiatives undertaken for the purpose of consolidating the duchies in their administrative and economic dimensions, utilizing innovative socio-systemic mechanisms such as the establishment of new towns, construction of castles and administrative reforms of both the Castellans and Weichbilds, as well as the promotion of migration by foreign knights. Yet another breakthrough took place when the Silesian duchies fell under either the direct or feudal dominion of the Bohemian Crown. Seeing as the House of Luxembourg was not interested in the creation of centralized institutions and did not interfere in internal relations between the duchies, institutional differences deepened. Unification policies took shape only within individual duchies, with the limitations of such policies and a focus on short-term solutions being evident. Attempts to make the administrative structures uniform were rare, which is especially evident in the context of incorporated areas. Rapid changes in the feudal fragmentation also proved a hindrance to unification activities. Remaining within a unified Church structure and single political organism was, however, a cohesive factor.
Keywords: medieval history; administrative structure; government of medieval Silesia